Property Ownership and Corruption: Effect on Sustainable Development of Africa - Olayinka, Olaniyi Felix (Economics & Law ISSN 2682-972X DOI:10.37708/el.swu.v3i1.2 Volume: III, Issue: I, Year: 2021, pp. 18-37, 2021)
Pre-colonial communities occupying the space now known as Africa reflected “paradise on earth” having men of integrity, selfless, with focus on community development. The bonding of man with land and the invocation of land - based - spiritual powers allowed for easy enforcement of good morals and conduct in communities. The partitioning of Africa, with the break of the existing social-cultural bonding and the consolidation under colonisation of communities in Africa made communal bonding un-sustainable. The African ubuntu concept gave way, turning an average African a potential drain on his community under a “winner takes all” syndrome, just as he grabs property indiscriminately. The western legal systems introduce private property ownership, but the legal systems in practice record huge breaches of the rule of law, truncation of justice and development. The paper precisely investigates whether development in Africa can be attained based on legal systems foreign to Africa, rather than through indigenous legal tradition.
Keywords: Indigenous legal tradition; Access to justice; Sustaining development